Design of Parcel Box Using RFID Technology with Arduino - Jason Teo Chang Cheng,; Mohd, Mohd Sabani (Multidisciplinary Applied Research and Innovation, 2026)
In this era of growing online shopping, secure and efficient delivery systems are very important. This paper presents the design and inplementation of a parcel box that uses RFID (Radio Frequency Identification) technolgy combined with an Arduino microcontroller. The primary objective is to build a security system by using RFID module. The core components of the system include an RFID reader, a 4x4 matrix membrane keypad, a red and a green LED, a solenoid door lock, and a 5V relay module, all controlled by an Arduino board. Each authorized user is provided with unique RFID tag. When an authorized tag is scanned, the Arduino verifies the tag and triggers the green LED, indicating successful authentication, and unlocks the parcel box via the solenoid lock controlled by the relay module. If an unauthorized tag is detected, the red LED lights up, and the box remains locked. Additionally, the 4x4 matrix membrane keypad allows users to enter a personal identification number (PIN) for an added layer of security. This dual-factor authentication mechanism ensures that only authorized users can access the parcel box, leading to greater security. The proposed design provides a low-cost and scalable solution for secure parcel handling, addressing common issues like package theft and missed deliveries. Experimental results show that the system is reliable and effective, making it suitable for residential uses. This parcel box design aims to enhance the security and efficiency of the last-mile delivery process, meeting the demands of modern e-commerce.